Fabricação de um circuito lock-in para a estabilização de frequência de diodo - Martins, Matheus do Amaral (Universidade Federal de São Carlos, 2021)
A cold atom experiment requires lasers with stable frequencies. In this work, we fabricated and characterized a lock-in circuit for frequency stabilization of a laser diode. The principle of stabilizing a physical quantity by feedback, particularly in the lock-in system, is discussed. The fabricated circuit is discussed, and its main characteristics are measured.
Lock-in circuit fabrication for the frequency stabilization of a diode laser
Keywords: Estabilização de frequência; Laser de diodo; Átomos frios; Frequency stabilization; Diode laser; Cold atoms; Lock-in; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::INSTRUMENTACAO ESPECIFICA DE USO GERAL EM FISICA